How does language play a role in intercultural communication today? Chapter review of intercultural communication in contexts, 8th edition by Judith N. Martin and Thomas K. Nakayama - Ayu Muhammad, Anugrah Puspita; Asbar, Asbar; Samsuddin, Samsuddin; Misnawati, Misnawati (Yayasan Cendekiawan Indonesia Timur, 2022)
This article is a review chapter of Judith N. Martin and Thomas K. Nakayama's book entitled